2014
DOI: 10.1177/0961203314529468
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian reserve in women with primary antiphospholipid syndrome

Abstract: Women suffering from PAPS possessed reduced ovarian reserve, with prevalence greater than 50%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 30 publications
2
27
1
3
Order By: Relevance
“…Both methods may be used in the ovarian reserve assessment [24]. The comparable results obtained herein and in accordance to other studies in autoimmune rheumatic diseases with high positive correlation between the two AMH assays [6,23,25,26] minimized the instability in terms of AMH Gen II ELISA values reported previously [27].…”
Section: Discussionsupporting
confidence: 93%
“…Both methods may be used in the ovarian reserve assessment [24]. The comparable results obtained herein and in accordance to other studies in autoimmune rheumatic diseases with high positive correlation between the two AMH assays [6,23,25,26] minimized the instability in terms of AMH Gen II ELISA values reported previously [27].…”
Section: Discussionsupporting
confidence: 93%
“…In previous studies, it was reported that AMH levels were more sensitive in indicating ovarian reserves, and, as the number of follicles decreased with increasing age, AMH levels also decreased [ 4 ]. In recent years, AMH has again been identified as a helper marker in the follow-up of ovarian reserves in women with rheumatic diseases [ 5 7 ]. However, we did not come across any study in the literature evaluating ovarian reserves in female FMF patients with AMH levels.…”
Section: Introductionmentioning
confidence: 99%
“…The confirmation of this association in future studies, therefore, could lead to the early diagnosis of this condition in many women. 29,31 Antiphospholipid antibody syndrome and obstetrics morbidity…”
Section: Antiphospholipid Antibody Syndrome and Primary Infertilitymentioning
confidence: 99%